PEMBIASAAN PAGI SEJAK MADRASAH DALAM MENANAMKAN PERILAKU RELIGIUS - Yulianingsih, Ulfa (FASHLUNA, 2023)
This research aims to review the implementation of children's morning habits since Madrasah to instill religious behavior. In this research, researchers used qualitative research with a library approach. referring to scientific sources such as books, journals and encyclopedias. In addition, the reference to the law on national standards for early childhood education contributes to the investigation of the importance of considering this research. The results of this research show that the implementation of habituation in forming religious behavior is carried out in a programmed manner in accordance with the educational calendar and teacher teaching schedule such as: Dhuha prayer, reading Asmaul Husna, praying, memorizing surahs, reciting the Al-Qur'an, Daily Infaq, Tahlil every Friday 'in the morning, and midday prayers in congregation, for obstacles in implementing morning habits to instill religious behavior in one's own parenting patterns in children, students' educational background, family, school and community environment, peers, facilities and infrastructure, to overcome these various obstacles, some Solutions include controlling, reward and punishment, adding facilities and infrastructure, socializing the importance of character education and discipline.